Optimasi Pola Tanam Irigasi Kaiti Samo Kabupaten Rokan Hulu Menggunakan Program Linier - Abror, Mukhlas; Fauzi, Manyuk; Saputra, M Efendi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
The main purpose of this study is to optimize the utilization of water resources and land in Kaiti Samo Irrigation Area of Rokan Hulu District through variations of crop patterns. Kaiti Samo Irrigation Area with 1654 Ha of potential area, the functional area is only 700 Ha. The processing of agricultural land at the location is also done twice a year with Padi-Padi-Bera crop pattern. Â  The research methode used is optimization study to obtain the maximum profits of farming results based on the optimal planting area using a linear program. The existing dependable volume and crops water requirements of each alternative crop pattern planned are used as restrictions/constrains as input for operation of linear program. The results of these calculations are expected to know the optimal planting area according to the crop pattern and crop season, also the greatest profits will be obtioned. Â  The results of one early planting alternative planned, crop pattern is obtained which get the greatest profits is Padiâ Padiâ Kacang Hijau at early planting November period I. The profits is Rp 8.829.000.000,00 with the planting area for crop season I: Padi = 1180 Ha, crop season II: Padi = 1180 Ha, crop season III: Kacang Hijau = 1140 Ha, and crop intensity 237%. Â  Key words : dependable volume, crop water requirement, crop pattern, optimization, linear program